Analysis of the Doha negotiations and the functioning of the World Trade Organization - Martin Khor (South Centre, 2010)
This paper discusses the principles and scope of activities of the world trade organization, addresses the imbalances in the existing rules and the problems faced by developing countries. Then it elaborated on various specific issues such as, the 'Singapore issues', labour and environmental standards, the 'development issues', market access negotiations and, at last, its functioning in decision-making system.
Keywords: 300